2022
DOI: 10.3233/jad-215313
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Retinopathy Predicts Risk of Alzheimer’s Disease: A Danish Registry-Based Nationwide Cohort Study

Abstract: Background: Retinal neurodegeneration is evident in early diabetic retinopathy (DR) which may be associated with other neurodegenerative diseases like Alzheimer's disease (AD). Objective: To investigate diabetes and DR as a risk marker of present and incident AD. Methods: A register-based cohort study was performed. We included 134,327 persons with diabetes above 60 years of age, who had attended DR screening, and 651,936 age- and gender-matched persons without diabetes. Results: At baseline, the prevalence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…The distribution of diabetes types in the population was determined by combining diagnostic codes (International Classification of Diseases 10 codes) for diabetes and codes for prescription (Anatomical Therapeutic Chemical Classification System codes) of insulin. Pedersen et al 18 19 We measured progression in both eyes separately. Consequently, some patients contribute with 1 eye and some with 2 eyes.…”
Section: Methodsmentioning
confidence: 99%
“…The distribution of diabetes types in the population was determined by combining diagnostic codes (International Classification of Diseases 10 codes) for diabetes and codes for prescription (Anatomical Therapeutic Chemical Classification System codes) of insulin. Pedersen et al 18 19 We measured progression in both eyes separately. Consequently, some patients contribute with 1 eye and some with 2 eyes.…”
Section: Methodsmentioning
confidence: 99%
“…Another study by Grauslund et al reported that individuals with diabetes without diabetic retinopathy were less likely to develop Alzheimer's disease compared to persons without diabetes. However, individuals with diabetic retinopathy had a 34% higher risk of incident Alzheimer's disease (Pedersen et al 2022). This might indicate that prevention or treatment of dementia could affect the risk of ocular complications in diabetics.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigating the association between DR and cognitive function all focused on DR as the independent factor, i.e., as a potential marker for present or incident CIND/AD. To this end, they found that patients with DR had increased prevalence (Ong et al, 2012 ; Liao et al, 2017 ) and incidence (Gupta et al, 2019 ) of CIND, as well as increased incidence of AD (Chen et al, 2016 ; Lee et al, 2019 ; Pedersen et al, 2022 ). A recent systematic review and meta-analysis support these results by concluding that having moderate DR or worse was strongly associated with cognitive impairment (Cheng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%